2015
DOI: 10.3390/jcdd2020093
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Electrocardiography Identifies Left Ventricular Systolic Dysfunction in Non-Ischemic Cardiomyopathy and Tracks Serial Change over Time

Abstract: Electrocardiogram (ECG)-based detection of left ventricular systolic dysfunction (LVSD) has poor specificity and positive predictive value, even when including major ECG abnormalities, such as left bundle branch block (LBBB) within the criteria for diagnosis. Although machine-read ECG algorithms do not provide information on LVSD, advanced ECG (A-ECG), using multiparameter scores, has superior diagnostic utility to strictly conventional ECG for identifying various cardiac pathologies, including LVSD. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The effect size was similar in patients with either nonischaemic or ischaemic cardiomyopathy. At its optimal cut off ≤ -2.04, Youden index J 95% CI ≤ -2.46 to ≤ -0.22), the 5-parameter score A-ECG for LVSD, previously validated for its diagnostic superiority over human ECG readers[ 23 ], had a higher AUC (0.71) than that of the spatial QRS-T angle for predicting a primary event, although the difference did not reach statistical significance. The LVSD A-ECG score as a continuous variable had an adjusted HR of 0.8 (95% CI 0.7 to 0.98) after adjusting the effects of the binary spatial QRS-T angle result, type II diabetes and LVEF.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect size was similar in patients with either nonischaemic or ischaemic cardiomyopathy. At its optimal cut off ≤ -2.04, Youden index J 95% CI ≤ -2.46 to ≤ -0.22), the 5-parameter score A-ECG for LVSD, previously validated for its diagnostic superiority over human ECG readers[ 23 ], had a higher AUC (0.71) than that of the spatial QRS-T angle for predicting a primary event, although the difference did not reach statistical significance. The LVSD A-ECG score as a continuous variable had an adjusted HR of 0.8 (95% CI 0.7 to 0.98) after adjusting the effects of the binary spatial QRS-T angle result, type II diabetes and LVEF.…”
Section: Resultsmentioning
confidence: 91%
“…The A-ECG parameters included: The posterior-to-leftward (P/L) QRS loop ratio within the derived vectorcardiographic horizontal plane (2.15 vs.1.15, p = 2x10 -6 , noting that this parameter has previously been correlated to invasively measured pulmonary artery pressures [ 21 , 22 ]); the spatial mean QRS-T angle (134 vs. 112°, p = 1.6x10 -4 ); various repolarisation vectors; and the aforementioned 5-parameter A-ECG score for LVSD (p = 4x10 -6 ). [ 23 ] The two echocardiographic parameters that after adjustment for multiplicity remained different were the left atrial (LA) volume and the LA/Aortic diameter ratio. Notable amongst the 14 echocardiographic parameters that were univariately different (p<0.05) were the aortic ELI (3.2 versus 2.6, p = 0.005 in those with versus without primary events) and aortic valve area (AVA), the dimensionless severity index (DSI, Vmax)[ 24 ], the (LVEDD/BSI), the tricuspid regurgitation (TR) jet maximum velocity, and LVEF.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly the A-ECG score for LVSD was also highly correlated with global longitudinal strain, itself known to be associated with increased risk of ventricular arrhythmia [41]. We have previously demonstrated that the A-ECG LVSD score, which itself incorporates results from the spatial QRS-T angle, has equal diagnostic sensitivity and higher specificity in the diagnosis of heart failure compared to human readers of a 12-lead ECG [23,42].…”
Section: Discussionmentioning
confidence: 99%
“…These included the spatial QRS-T angle, the sum absolute QRST integral (SAI QRST) [6,25], the posterior-to-lateral (P/L) QRS loop ratio [21], and the 5-parameter A-ECG score for LVSD [23]. All of these parameters had high rewiring scores when comparing patients with primary events to those without events.…”
Section: Graph Analysismentioning
confidence: 99%
See 1 more Smart Citation